"Cities go smart!": A system dynamics-based approach to smart city conceptualization. (1st September 2021) - Nunes, Simão A.S.; Ferreira, Fernando A.F.; Govindan, Kannan; Pereira, Leandro F.
Abstract: The world's population has grown rapidly. Thus, new challenges have arisen in terms of people's quality of life, natural resources renewal, and urban environment sustainability. The smart city concept was developed to deal with these challenges by incorporating new technologies in order to find solutions that preserve cities' environment while promoting their residents' wellbeing. However, for cities to be truly "smart", they should be evaluated, and, to that end, determinants that facilitate their creation need to be identified. This study thus sought to combine cognitive mapping and the system dynamics approach to find which factors foster smart city success, as well as the cause-and-effect relationships among these determinants. In two groupwork sessions, a panel of experts identified a wide range of smart city determinants and analyzed the dynamics of their relationships. The results were validated by the panel members and senior representatives of Cascais and Évora City Councils, Portugal, who confirmed that the analysis system developed provides a deeper understanding of this research context. The advantages and limitations of the proposed framework are also discussed.